Flood Disaster Risk Analysis for the Community in Penjalin Village, Brangsong Sub-District, Kendal Regency - Masnun, Masnun; Ghassani, Dewi Bussaina; Rahayu, Umi; Wijaya, Tenardhy Arya (Peneliti.net, 2025)
The aim of this research is to find out the impact of the flood that occurred in Penjalin Village, Brangsong Distric, Kendal Regency. This research uses a direct interview method with the people in Penjalin Villagofe based on the planned rainfall and the planned discharge obtained from the calculation results of a method. This research aims to analyze floods using two methods, namely using the Gumbel method calculation formula and the Type III Log Person method. The results obtained from calculations using the Gumbel method formula, the planned rainfall for the 2-year re-economy period is 195,422 mm while the 5 year repeat period is 255,547 mm and 10-year return period of 278,719 mm. The results obtained from calculations using the Log Person Type III formula are, The planned rainfall for the 2-year return period is 199,96 mm, while the 5-year return period is 219, 352 mm, and the 10-year return period is 262,63 mm. The distribution used in this calculation is Log Person Type III because it better meets the requirements, namely Cs ≠ 0 compared to calculations using the Gumbel method. The calculation of the rain concentration time using the Kirpich method was 0,431 hours, and in determining the intensity of rain using the method, the results obtained were I2 = 121,482 mm/hour, I5 = 133,264 mm/hour, and I10 = 159,572 mm/hour. In determining the planned discharge using rational methods, the results obtained are, Q2 = 10,638 x 10-4m3/s, Q5 = 11,66 x 10-4m3/s, and Q10 = 13,97 x 10-4m3/s. From this research, it can be concluded that the planned rainfall and planned discharge from the 2-year return period, 5-year return period, and 10-year return period always increase.